Research progress of 3D printing combined with thermoplastic foaming - Sun, Bin; Wu, Lixin (Frontiers in Materials, 2022)
Thermoplastic foam additive manufacturing is a brand-new industry that perfectly combines the advantages of polymer foaming with AM. Designing multifunctional components with additive manufacturing gives designers great flexibility, while foaming reduces the weight of materials and costs. The combination of the two allows for the creation of lightweight structural and functional items with differentiated physical properties. This one-of-a-kind and innovative approach can be achieved in the printed section. 3D printing foam, on the other hand, is still in its infancy. This review examines the respective functions and applications of additive manufacturing and foaming before attempting to summarize four commonly used 3D printing methods at this stage:1) hierarchical cellular scaffolds; 2) composite printing foam; 3) post-foaming of printed solid scaffolds; 4) in-situ foam 3D printing.